2015
DOI: 10.1148/radiol.2015142467
|View full text |Cite
|
Sign up to set email alerts
|

Advanced High-Grade Serous Ovarian Cancer: Frequency and Timing of Thoracic Metastases and the Implications for Chest Imaging Follow-up

Abstract: Thoracic metastases in advanced HGSC rarely occur before abdominal disease, and first thoracoabdominal metastases are invariably visible on abdominal images. Therefore, cross-sectional chest imaging may be deferred until development of abdominal disease, with minimal risk of missing thoracic metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Use of stage III HGSC allowed a more homogeneous population and represents the largest proportion of patients with ovarian cancer. Of the 88 patients included in the present study, 19 were included in our prior report in which we assessed the frequency and associations of thoracic metastases; however, there is no overlap between the objectives and methods of the prior and present study [11]. In the prior study, the metastatic spread was recorded after the primary cytoreductive surgery whereas the present study focuses on the presence of supradiaphragmatic lymphadenopathy on the baseline CT at presentation.…”
Section: Subjects and Settingmentioning
confidence: 99%
“…Use of stage III HGSC allowed a more homogeneous population and represents the largest proportion of patients with ovarian cancer. Of the 88 patients included in the present study, 19 were included in our prior report in which we assessed the frequency and associations of thoracic metastases; however, there is no overlap between the objectives and methods of the prior and present study [11]. In the prior study, the metastatic spread was recorded after the primary cytoreductive surgery whereas the present study focuses on the presence of supradiaphragmatic lymphadenopathy on the baseline CT at presentation.…”
Section: Subjects and Settingmentioning
confidence: 99%
“…Of these, 256 had pathologically proven serous ovarian cancer (both low and high grade) and 12 were excluded due to metastatic nonovarian cancer or inadequate medical records, leaving 244 in our final patient population (median age 6 standard deviation, 59 years 6 10.7; median follow-up, 44 months; interquartile range [IQR], 27-70) (Fig 1). Of these, we have previously reported the metastatic spread, with a focus on thoracic metastases, in 186 patients with high-grade serous to optimize the use of cross-sectional chest imaging; however, we did not evaluate the presence or absence of LPI or the prognostic importance of the different patterns of hepatic involvement (14).…”
mentioning
confidence: 99%
“…We have recently shown that thoracic metastases in patients with ovarian cancer typically develop late in the disease course and almost always occur with preexisting or prior abdominal disease (34). Moreover, the presence of disease on abdominal imaging was the only factor independently associated with thoracic metastases, and the initial thoracoabdominal metastases were almost always visible on abdominal imaging (34).…”
Section: Metastatic Surveillance and Evidence-based Imagingmentioning
confidence: 99%
“…Moreover, the presence of disease on abdominal imaging was the only factor independently associated with thoracic metastases, and the initial thoracoabdominal metastases were almost always visible on abdominal imaging (34). Therefore, it seems that there is an opportunity to reduce the utilization of chest CT in patients with ovarian cancer with a consequent reduction in the associated costs and radiation dose, especially to the breast tissue (3233).…”
Section: Metastatic Surveillance and Evidence-based Imagingmentioning
confidence: 99%